Dark matter and possible particle solutions - Buza, Guri K. (Matrika, 2022)
The hypothesis of dark matter is entertained by stating some corresponding observational evidence. Following that line of thought, using the standard cosmological principles and gravitational laws, the Friedmann equations are obtained in terms of energy densities. That is called-for, since the values of energy densities are estimated using the standard cosmological model, where dark matter is included. After a brief discussion of possible candidates for dark matter, the weakly interacting massive particles (WIMPs) are treated in more detail. They are considered as a favourable candidate because the assumption that dark matter has a relic density, after decoupling in the early stages of the Universe, is in harmony with the properties of WIMPs. Finally, a brief summary covers the ongoing experimental search for the direct and indirect detection of dark matter.
Keywords: cosmology; dark matter; delci WIMP; detection; iskanje temne snovi; kozmologija; temna snov; WIMP particles